2008
DOI: 10.3113/fai.2008.0171
|View full text |Cite
|
Sign up to set email alerts
|

Medial Malleolar Osteotomy for the Correction of Varus Deformity During Total Ankle Arthroplasty: Results in 15 Ankles

Abstract: Medial malleolar lengthening osteotomy is an easy technique for the realignment of the varus ankle at the time of total ankle arthroplasty, and served as an alternative to medial ligament release or lateral ligament reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(60 citation statements)
references
References 19 publications
0
55
1
4
Order By: Relevance
“…8,9,[19][20][21][22][23][24][25][26] One cannot isolate many studies reporting on outcomes of TARs combined with osteotomies, as these procedures are part of the whole spectrum of surgery performed for ankles with greater than 10 coronal plane deformity. Doets and colleagues 20 reported on his series of 15 TARs in varus ankles, requiring a medial malleolar lengthening osteotomy.…”
Section: Clinical Results In the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…8,9,[19][20][21][22][23][24][25][26] One cannot isolate many studies reporting on outcomes of TARs combined with osteotomies, as these procedures are part of the whole spectrum of surgery performed for ankles with greater than 10 coronal plane deformity. Doets and colleagues 20 reported on his series of 15 TARs in varus ankles, requiring a medial malleolar lengthening osteotomy.…”
Section: Clinical Results In the Literaturementioning
confidence: 99%
“…2). 15,16,20 One other option for larger varus deformity is the "plafondplasty," described by Ryssman and Myerson. 15 The osteotomy is guided from the supramalleolar region to the plafond, and bone graft is used to lengthen the medial wall of the ankle.…”
Section: Intra-articular Deformitymentioning
confidence: 98%
See 1 more Smart Citation
“…Good results have, however, recently been reported following TAR in patients with a hindfoot deformity of up to 30°. 16 Although many additional procedures are known, only a few series have included the results of TAR performed with additional operations 8,17,18 Hintermann et al 8 carried out 43 additional procedures simultaneously with 122 TARs using the Hintegra prosthesis, and had a good or excellent result in 82% and a revision rate of 6.6% after a mean of 18.9 months. In a follow-up study, including 271 cases with a mean follow-up of 36 months, the revision rate was 14.4%.…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up study, including 271 cases with a mean follow-up of 36 months, the revision rate was 14.4%. 18 Doets et al 17 developed a lengthening osteotomy of the medial malleolus and reported 12 excellent or good results in 14 ankles followed for more than two years. However, if they failed to correct the hindfoot varus deformity at the time of TAR, a revision procedure was required.…”
Section: Discussionmentioning
confidence: 99%